Impact of Migrant Workers to the Family Economic Status, Educational Level, and Child Health - BASROWI, BASROWI (Journal of Research in Educational Sciences; Vol 10 No 12 (2019): JRES Volume X Issue 12 Winter 2019DO - 10.14505//jres.v10.12.03, 2020)
The majority of women in Indonesia in general and Lampung in particular have not found decent jobs and have sufficient income. To get a decent income they choose to become migrant workers. The purpose of this is to describe the effect of remittance on the economic level of the migrant workers' families, the length of time the child is educated, and the health level of the child. This study uses a survey approach to migrant workers and former migrant workers from Lampung Province. The results of the study are original findings about the use of remittance models and policy recommendations that can be used for all parties involved in women migrant workers. The results of the study concluded that remittances had a positive and significant impact on improving the family's economy, children's education duration, and children's health level.